KRITIK SOSIAL DALAM NOVEL ANAK RANTAU KARYA AHMAD FUADI (TINJAUAN SOSIOLOGI SASTRA) - safriyanti; H.M Yazid; Nurlailatul Qadriani (Cakrawala Listra: Jurnal Kajian Sastra, Bahasa, dan Budaya Indonesia, 2024)
This study examines novels that tell about the social realities of the people of Minang that occur in modern times. Anak Rantau's novel by Ahmad Fuadi is interesting to be analyzed using the Sociology Literature approach of Genetic structuralism,as the novel contained criticisms of social problems that occur in the Minangkabau region. The problems investigated in this study are (1) how the social structure and world view of the author in the Anak Rantau novel, (2) how social criticism in the Anak Rantau novel. In connection with this problem, this study aims (1) to describe the social structure and worldview of the author in the novel Anak Rantau, (2) to describe social criticism in the Anak Rantau novel. The research method used are descriptive qualitative and dialectical methods. Types of research are namely library research and interview methods. The results showed that (1) the social structure found in Anak Rantau's novel included cooperation, cultural and religious systems and knowledge systems. The author's world view in Anak Rantau's novel is a concern for shifting cultural values ??in Minangkabau society. (2) the social criticism found in Anak Rantau's novel includes, the author as a representative of the collective subject sees a social problem that occurs in the surrounding environment, namely, the shift of the surau function that was used as a center of education by children towards the maturity and existence of Ninik Mamak did not working properly. Keywords: Social Criticism, Social Problems, Sociology of Literature, Genetic Structuralism